Women and Political Leadership in Islam: Ma'nā-cum-Maghzā Critical Hermeneutic Study - Muhammad Fauzinuddin Faiz; Nurul Huda; Akhmad Khubby Ali Rohmad; Muhammad Solikhudin; Sheyla Nichlatus Sovia (Islamica: Jurnal Studi Keislaman, 2023)
This paper describes and analyzes the textual-contextual h}adīth on the prohibition of women’s leadership in the public sphere. This study is a critical hermeneutic with the theory of ma‘nā-cum-maghzā, by making the literal origin (historical meaning, explicit) the starting point for understanding the central message of the text (implied meaning). The results of this paper indicate that women may become leaders in public affairs because textually and linguistically, the word lan yufliḥ, which means ‘will not be successful,’ in the h}adīth does not apply permanently (mu’abbad), but only temporally (mu’aqqat). Contextually, the h}adīth prohibited women from becoming leaders because the condition of women at the time of the h}adīth did not allow them to handle social affairs due to the lack of knowledge and experience and the existence of deceit and greed, which could happen to anyone who had ambitions of power, men as well as women. Meanwhile, nowadays, many women have the expertise, knowledge, and managerial-organizational experience to support these matters.